2007
DOI: 10.1016/j.nlm.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and progestins enhance spatial learning of intact and ovariectomized rats in the object placement task

Abstract: Steroid modulation of cognitive function has focused on estrogen (E 2 ), but progestins naturally covary with E 2 and may also influence cognitive performance. Spatial performance in the object placement task over endogenous hormonal states in which E 2 and progestins vary, and when E 2 and/ or progestins were administered, was examined. Experiment 1: Rats in proestrus or estrus had significantly better performance in the object placement task than did diestrous rats. Experiment 2: Rats in the third trimester,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
219
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 216 publications
(242 citation statements)
references
References 78 publications
18
219
4
1
Order By: Relevance
“…While the effect of estradiol on false memories has not yet been directly examined in humans, recent animal studies have demonstrated improved object recognition memory in rats following estradiol treatment (e.g. Frye et al, 2007;Inagaki et al, 2010;Jacome et al, 2010). In contrast to previous studies investigating recognition performance, the present findings suggest that estradiol does not improve false recognition in humans in general.…”
Section: Estradiol Reduces False Recognition In Highly Schizotypal Wocontrasting
confidence: 99%
“…While the effect of estradiol on false memories has not yet been directly examined in humans, recent animal studies have demonstrated improved object recognition memory in rats following estradiol treatment (e.g. Frye et al, 2007;Inagaki et al, 2010;Jacome et al, 2010). In contrast to previous studies investigating recognition performance, the present findings suggest that estradiol does not improve false recognition in humans in general.…”
Section: Estradiol Reduces False Recognition In Highly Schizotypal Wocontrasting
confidence: 99%
“…Interestingly, cell proliferation was reduced with coadministration of DPN and PPT [88]. Furthermore, ERα in the hippocampus has been suggested to influence neuronal morphology by stimulating dendritic branching [89], whereas spatial, hippocampus-dependent learning has been shown to be mediated by both ERα [90][91] and ERβ [82,[92][93].…”
Section: The Role Of Erα (And Erβ) For Functional Effects Of Estogensmentioning
confidence: 99%
“…Although many studies showed that OVX is associated with poorer behavioral and cognitive performance, including tasks considered relevant to schizophrenia such as social interaction and object recognition (Barnes et al, 2006;Frye, 2001;Frye et al, 2006bFrye et al, , 2007Frye and Rhodes, 2006a;Paris and Frye, 2008), the study of the estrogen hypothesis using animal models of schizophrenia has been limited. Some support derives from studies showing that estrogen affects prepulse inhibition (PPI) (Gogos et al, 2009;Gogos and Van den Buuse, 2004;Koch, 1998;Vaillancourt et al, 2002;Van den Buuse and Eikelis, 2001), a measure of sensorimotor gating whose disruption is considered to model sensorimotor deficits in schizophrenia, as well as the response to the pro-psychotic drugs amphetamine and cocaine (Becker and Beer, 1986;Becker and Rudick, 1999;Earley and Leonard, 1978;Gibbs et al, 1998;Naik et al, 1978;Segarra et al, 2009).…”
Section: Introductionmentioning
confidence: 99%